Exemestane metabolites suppress growth of estrogen receptor-positive breast cancer cells by inducing apoptosis and autophagy: A comparative study with Exemestane. (December 2015) - Amaral, Cristina; Lopes, Andreia; Varela, Carla L.; da Silva, Elisiário Tavares; Roleira, Fernanda M.F.; Correia-da-Silva, Georgina; Teixeira, Natércia
Highlights: Effects of exemestane metabolites in breast cancer cells are different from exemestane. Metabolites induced cell cycle arrest and apoptosis in sensitive breast cancer cells. Metabolites induced autophagy as a promoter mechanism of apoptosis. Metabolites can sensitize AIs-resistant breast cancer cells, inducing apoptosis. Exemestane efficacy in breast cancer treatment may be dependent on its metabolites. Abstract: Around 60–80% of all breast tumors are estrogen receptor-positive. One of the several therapeutic approaches used for this type of cancers is the use of aromatase inhibitors. Exemestane is a third-generation steroidal aromatase inhibitor that undergoes a complex and extensive metabolism, being catalytically converted into chemically active metabolites. Recently, our group showed that the major exemestane metabolites, 17β-hydroxy-6-methylenandrosta-1, 4-dien-3-one and 6-(hydroxymethyl)androsta-1, 4, 6-triene-3, 17-dione, as well as, the intermediary metabolite 6β-Spirooxiranandrosta-1, 4-diene-3, 17-dione, are potent aromatase inhibitors in breast cancer cells. In this work, in order to better understand the biological mechanisms of exemestane in breast cancer and the effectiveness of its metabolites, it was investigated their effects in sensitive and acquired-resistant estrogen receptor-positive breast cancer cells. Our results indicate that metabolites induced, in sensitive breast cancer cells, cell cycle arrest and apoptosis via mitochondrial pathway, involving caspase-8 activation. Moreover, metabolites also induced autophagy as a promoter mechanism of apoptosis. In addition, it was demonstrated that metabolites can sensitize aromatase inhibitors-resistant cancer cells, by inducing apoptosis. Therefore, this study indicates that exemestane after metabolization originates active metabolites that suppress the growth of sensitive and resistant breast cancer cells. It was also concluded that, in both cell lines, the biological effects of metabolites are different from the ones of exemestane, which suggests that exemestane efficacy in breast cancer treatment may also be dependent on its metabolites.